Temperature-dependent variation in the extent of methylation of ribosomal proteins L7 and L12 in Escherichia coli. - Chang, F N (1978)
The amount of epsilon-N-monomethyllysine in ribosomal proteins L7 and L12 in Escherichia coli is dependent upon the cell growth temperature. At 37 degrees C or above, very small amounts were detected. Dramatic increase in the content of epsilon-N-monomethyllysine in these proteins was observed when the growth temperature was lowered.